2005
DOI: 10.1111/j.0014-3820.2005.tb01761.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Monophyletic Origin of Triploid Clones of the Amazon Molly, Poecilia Formosa

Abstract: Abstract. Asexual reproduction in vertebrates is rare and generally considered an evolutionary dead end. Asexuality is often associated with polyploidy, and several hypotheses have been put forward to explain this relationship. So far, it remains unclear whether polyploidization in asexual organisms is a frequent or a rare event. Here we present a field study on the gynogenetic Amazon molly, Poecilia formosa. We used multilocus fingerprints and microsatellites to investigate the genetic diversity in 339 diploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 37 publications
5
49
0
Order By: Relevance
“…This was mirrored in a very high clonal diversity of the triploid form. Similar phenomena have previously been observed in the triploid specimens from Japan (61 clonal lines among 219 specimens, using only three microsatellite loci) (Ohara et al 2003) and in two other polyploid fish species: Leuciscus alburnoides (Steindachner) (Alves et al 2001) and P. formosa (Lampert et al 2005;Schories et al 2007). These observations are particularly interesting as genotype variability in asexual organisms can be generated only through polyphyletic origin (Vrijenhoek 2006), by mutation, and from incorporation of a sexually produced genome in each generation (Alves et al 2001).…”
Section: The Origin Of Croatian Cac Populationssupporting
confidence: 82%
See 1 more Smart Citation
“…This was mirrored in a very high clonal diversity of the triploid form. Similar phenomena have previously been observed in the triploid specimens from Japan (61 clonal lines among 219 specimens, using only three microsatellite loci) (Ohara et al 2003) and in two other polyploid fish species: Leuciscus alburnoides (Steindachner) (Alves et al 2001) and P. formosa (Lampert et al 2005;Schories et al 2007). These observations are particularly interesting as genotype variability in asexual organisms can be generated only through polyphyletic origin (Vrijenhoek 2006), by mutation, and from incorporation of a sexually produced genome in each generation (Alves et al 2001).…”
Section: The Origin Of Croatian Cac Populationssupporting
confidence: 82%
“…Highly polymorphic microsatellites have been proven to be particularly valuable for parentage identification, stock discrimination and population structure analysis (O'Connell and Wright 1997; Guo and Gui 2008), and have also been used to investigate clonal diversity and clonal identification in unisexual fish Poecilia formosa (Girard) (Lampert et al 2005) and in the polyploid C. a. gibelio (Ohara et al 2003;Guo and Gui 2008;Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In P. formosa, triploids most probably have arisen only two times during the evolutionary history of the species (Schories et al 2007). They show an unexpectedly low genotypic diversity and are most probably of recent origin (Lampert et al 2005). Triploids in other unisexual species show higher levels of genotypic variability leading to the assumption that they are derived from several introgression events (Alves et al 2001;Janko et al 2003).…”
Section: Hybridization Leading To the Intro-gression Of Paternal Genementioning
confidence: 99%
“…A higher genotypic variability, however, could not be found in triploids. In a microsatellite study of several hundreds of field-caught individuals, it was found that the triploid clones in one river system have a much lower genotypic variability than the diploids from the same system and are most probably of monophyletic and recent origin (Lampert et al 2005).…”
Section: Hybridization Leading To the Intro-gression Of Paternal Genementioning
confidence: 99%
“…They have been proven to be particularly valuable for parentage, stock discrimination, population genetics, and genome mapping, because of the high levels of polymorphism (O'Connell and Wright 1997). Microsatellite markers have also proven their value in studies of triploid species, for example evolution analysis in the Amazon molly (Poecilia formosa) (Lampert et al 2005), clonal identification in Japanese gibel carp (Carassius auratus langsdorfii) (Kenichi et al 2003), etc. Traditionally, SSR isolation has relied on the screening of genomic libraries using repetitive probes and sequencing of positive clones in order to develop locus-specific primers, which is obviously a tedious task but can result in numerous SSRs being obtained.…”
Section: Introductionmentioning
confidence: 99%